Mucosal-Associated Invariant T Cells in Multiple Sclerosis: The Jury is Still Out - Treiner, Emmanuel; Liblau, Roland S. (Frontiers in Immunology, 2015)
The immune system is strongly implicated in the pathophysiology of multiple sclerosis (MS), as demonstrated by the efficacy of therapies targeting various components of adaptive immunity. However, the disease still progresses despite these treatments in many patients, while others experience life-threatening adverse effects, urging for the discovery of new medications targeting other pathways. Decades of work have highlighted the prominent role of CD4 T cells in MS, but more recent data demonstrate the involvement of CD8 T cells as well. The existence of both pathogenic and protective CD8 T cells subsets has been suggested, adding an additional layer of complexity to the picture. Mucosal-Associated Invariant T cells (MAIT) are innate-like lymphocytes that make up to 25% of CD8 T cells in healthy subjects. They are specific for conserved microbial ligands and may constitute an important barrier against invasive bacterial and fungal infection. An increasing number of reports also suggest their possible involvement in chronic inflammatory diseases, including MS. MAIT cells could participate through their ability to produce IFNgamma and/or IL-17, two major cytokines in the pathogenesis of several chronic inflammatory/autoimmune diseases. However, the mechanisms by which MAIT cells could be activated in these sterile conditions are not known. Furthermore, contradictory observations have been made, reporting either a protective or a pro-inflammatory behavior of MAIT cells in MS or its murine model, experimental autoimmune encephalomyelitis (EAE). In this review article, we will describe the current knowledge on MAIT cells biology in health and disease, and discuss the possible mechanisms behind their role in MS. The specific features of this new nonconventional T cell subset make it an interesting candidate as a biomarker or as the target of immune-mediated intervention.